Philosophy, rights and natural law essays in honour of Knud Haakonssen - Hunter, Ian, 1949-; Whatmore, Richard; Haakonssen, Knud, 1947- (Edinburgh scholarship online., 2019)
Over his long and illustrious career, Knud Haakonssen has explored the role of natural law in formulating doctrines of obligation and rights in accordance with the interests of early modern polities and churches. The essays collected in this volume range across this exciting and contested field. These 13 new essays acknowledge Haakonssen's immense academic achievement and give us new insights into the cultural and political role of law and rights in a variety of historical contexts and circumstances. --